2014
DOI: 10.1007/s00213-014-3728-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imperatorin on scopolamine-induced cognitive impairment and oxidative stress in mice

Abstract: RationaleImperatorin, a naturally occurring furanocoumarin, inactivates gamma-aminobutyric acid transaminase and inhibits acetylcholinesterase activity.ObjectivesThe purpose of our experiment was to examine the influence of imperatorin on cognitive impairment and oxidative stress in the brain induced by scopolamine in male Swiss mice.MethodsIn the present studies, we used scopolamine-invoke memory deficit measured in passive avoidance (PA) paradigm as an animal model of Alzheimer disease (AD).ResultsOur findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 59 publications
5
97
0
1
Order By: Relevance
“…Imperatorin (IPT, Figure 1) is a natural constituent commonly existing in plants of the Umbelliferae family, such as Peucedanum praeruptorum and Angelica dahurica [8]. IPT shows a broad pharmacological activities including anti-seizure, vasodilatation, antitumor, antimicrobial, anti-inflammatory, and analgesic effects [8][9][10]. However, to the best of our knowledge, there is no information on the effects of IPT on allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Imperatorin (IPT, Figure 1) is a natural constituent commonly existing in plants of the Umbelliferae family, such as Peucedanum praeruptorum and Angelica dahurica [8]. IPT shows a broad pharmacological activities including anti-seizure, vasodilatation, antitumor, antimicrobial, anti-inflammatory, and analgesic effects [8][9][10]. However, to the best of our knowledge, there is no information on the effects of IPT on allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…MDA, HNE, or TBARS were enhanced in all of those models in the cerebral cortex or/and hippocampus or/and the whole brain [237][238][239][240][241][247][248][249][250][251][252][253][254][255]. Oxidative modification of proteins has also been demonstrated in the cortex and whole brain homogenate of transgenic AD mice [253,255] and in the cerebral cortex and hippocampus of an Aβ 1-42 mouse model [247].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Furthermore, the activities of enzymes connected with GSH metabolism, such as GPx and GR, and the enzymes involved in antioxidant defense (SOD and CAT) were reduced in the hippocampus and cerebral cortex in pharmacological and genetic models [237,238,241,248,249,[254][255][256]. It should be noted that some studies demonstrated no change in CAT and SOD activity in whole brain lysates in Wistar rats in the streptozotocin model [240], while enhanced SOD, GPx, and GR were observed in the mouse cerebral cortex and hippocampus following i.c.v.…”
Section: Antioxidant Defense Biomarkersmentioning
confidence: 99%
“…Therefore, the representative extract of liquiritin and imperatorin lays an anti-inflammatory medicinal material foundation for development of the Fengshiding dropping pill. In addition, several methods, including organic solvent extraction, microwave-assisted extraction, 5 and ultrasonicassisted extraction (UAE), 6 have been widely employed for the extraction of single herb. However, few reports have focused on combination extraction process of Radix glycyrrhizae and Angelica dahurica (Fisch.)…”
Section: Introductionmentioning
confidence: 99%